Social Project: Tingkatkan Kepedulian Sesama dengan Bakti Sosial di Panti Asuhan Annisa Pekanbaru - Maya Rizki Sari; Masril Masril; Hanifah Hanifah; Ayu Wahyuni; Lisda Dhia Pratiwi; Nilpa Anggraini; Rodiatul Mukaramah; Rizkinisa Afsyah; Nadia Rahma Sari (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
Social activity or better known as baksos (in bahasa) is an activity that manifests a sense of humanity between human beings. As fellow human beings, we are obliged to help each other, especially those who are less fortunate than us. Therefore, through this social service, we visited the orphanage with the aim of sharing and caring for those in need. This activity is a collaboration between lecturers and students which was carried out at the Annisa Orphanage Pekanbaru together with 26 children and 1 administrator of the Annisa Orphanage along with 2 representatives of HIMMARI (Riau Mahaputra Student Association). The form of activities carried out is in the form of making works and providing basic necessities. The results of this activity show that caring for others can be established, one of which can be improved by social projects in the form of social services. This is important to do considering the urgency of caring for each other.